Causes and outcomes in studies of fear of childbirth: A systematic review. Issue 2 (April 2019) - Dencker, Anna; Nilsson, Christina; Begley, Cecily; Jangsten, Elisabeth; Mollberg, Margareta; Patel, Harshida; Wigert, Helena; Hessman, Eva; Sjöblom, Helen; Sparud-Lundin, Carina
Abstract: Problem: Fear of childbirth negatively affects women during pregnancy and after birth. Aim: To summarise the findings of published studies regarding possible causes/predisposing factors and outcomes of fear of childbirth for childbearing women. Design: A systematic review, searching five databases in March 2015 for studies on causes/predisposing factors and outcomes of fear of childbirth, as measured during pregnancy and postpartum. Quality of included studies was assessed independently by pairs of authors. Data were extracted independently by reviewer pairs and described in a narrative analysis. Findings: Cross-sectional, register-based and case-control studies were included (n = 21). Causes were grouped into population characteristics, mood-related aspects, and pregnancy and birth-related aspects. Outcomes were defined as mood-related or pregnancy and birth-related aspects. Differing definitions of fear of childbirth were found and meta-analysis could only be performed on parity, in a few studies. Conclusions: Stress, anxiety, depression and lack of social support are associated with fear during pregnancy. Need for psychiatric care and presence of traumatic stress symptoms are reported outcomes together with prolonged labour, longer labours, use of epidural and obstetric complications. Nulliparous and parous women have similar levels of fear but for different reasons. Since the strongest predictor for fear in parous women is a previous negative birth experience or operative birth, we suggest it is important to distinguish between fear of childbirth and fear after birth. Findings demonstrate the need for creating woman-centred birthing environments where women can feel free and secure with low risk of negative or traumatic birth experiences and consequent fear.